2012
DOI: 10.1016/j.cct.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Applying the ecological model of behavior change to a physical activity trial in retirement communities: Description of the study protocol

Abstract: OBJECTIVES To describe the intervention protocol for the first multilevel ecological intervention for physical activity in retirement communities that addresses individual, interpersonal and community influences on behavior change. DESIGN A cluster randomized controlled trial design was employed with two study arms: a physical activity intervention and an attention control successful aging condition. SETTING Sixteen continuing care retirement communities in San Diego County. PARTICIPANTS Three hundred tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…Participants (N = 307) were older adults living in 11 continuing care retirement communities in San Diego County who completed a baseline measurement as part of a randomized controlled trial (Multilevel Intervention for Physical Activity in Retirement Communities (17). Details of the trial can be found elsewhere (17).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants (N = 307) were older adults living in 11 continuing care retirement communities in San Diego County who completed a baseline measurement as part of a randomized controlled trial (Multilevel Intervention for Physical Activity in Retirement Communities (17). Details of the trial can be found elsewhere (17).…”
Section: Participantsmentioning
confidence: 99%
“…Details of the trial can be found elsewhere (17). The study was approved by the University of California, San Diego Institutional Review Board.…”
Section: Participantsmentioning
confidence: 99%
“…As such, these types of measures cannot directly be used to predict behavior in a given environment. Intervention studies, however, with GPS assessing changes in PA locations after local environment improvements will provide better evidence of causality(20). However, they will allow a wealth of new research questions focused on better matching of behavior and environment, resulting in more specific assessments of PA as related to locations, times, and behaviors.…”
Section: Conclusion and Moving Forwardmentioning
confidence: 99%
“…A key tenet of ecological models is that interventions that target multiple levels of influence (e.g., individual, social, and environmental) should be more effective in changing behavior than those that target only one level [4]. There have been a limited number of multi-level interventions focusing on the promotion of physical activity among adults [57] and, to our knowledge, only one study used a randomized controlled design [6]. When considering interventions for cancer prevention, a fewer programs have used the ecological approach to inform program development.…”
mentioning
confidence: 99%